The wage-price pass-through in the euro area: Does the growth regime matter? - Elke Hahn (European Central Bank (ECB), 2020)
This paper explores whether the transmission mechanism between wages and prices in the euro area is affected by the growth regime. Since the great financial crisis inflation developments have posed major puzzles to economists as inflation declined by less than was widely expected during the past recessions and rose by less during the subsequent recoveries. This paper analyses whether the wage-price pass-through may have contributed to these inflation puzzles. Applying the Threshold VAR model proposed by Alessandri and Mumtaz (2017) to the analysis of the wage-price pass-through, the paper examines whether the transmission mechanim of different types of shocks differs between recessions and expansions. The results point to differences in the wage-price pass-through between growth regimes for demand shocks but not for wage mark-up shocks. They show a much smaller response of prices relative to wages, i.e. a smaller wage-price pass-through, for demand shocks in recessions than in expansions. This is accounted for by a smaller relative response of profit margins. More generally, the results suggest that the slope of the price Phillips curve flattens in recessions on account of the lower wage-price pass-through, while the wage Phillips curve appears to be broadly stable across growth regimes. Overall, the results contribute to solve or diminish the puzzle of the missing disinflation of the past two recessions suggesting that inflation should be expected to recede by less during recessions than indicated by standard linear models.
Keywords: C32; E31; J30; 330; Euro area inflation; wage-price pass-through; growth regimes; threshold VAR